Proses Pembuatan Gelatin dari Kulit Kepala Sapi dengan Proses Hidrolisis Menggunakan Katalis HCl - Tunjung Wahyu Widayati (Prosiding Seminar Nasional Teknik Kimia "Kejuangan", 2015)
Cow leather is widely used as raw material for shoes, jackets, automobile n bag accessories too. But the skin of cow head (scalp) is not widely used. Actually that thing as a potensial and good materials for making gelatin. Gelatin used as a filler constituent in the food industries such as candy, butter and cheese,cakes, bread and meat meals industry. As diversification benefits and increase the economic value, our research done to make gelatin from cow scalp (head of cowhide).Experiment production of gelatin made with 15 gram of starch hydrolizing scalp cow in 400 mL water using HCl catalyst.influence the observes experimental variables is the ratio of reagents, temperature and time of hydrolysis and concentration ol catalyst solution HCl.The experiment result showed that the best condition for the hydrolysis process of scalp cow was at 6 hours at 90oC temperature, using 1,25 mL of 36,5 % HCl catalystwith gelatin production to 7,562 gram.